Alloplastic or autogenous reconstruction of the TMJ - Andrew J. Sidebottom (Journal of Oral Biology and Craniofacial Research)
Reconstruction of the irreparably damaged temporomandibular joint (TMJ) is dependent on the cause of damage and the patient's age. In childhood the current preference is for autogenous reconstruction which can potentially “grow” with the child. This is either with soft tissue interposition (temporalis fascial interposition), local osteotomy, distraction osteogenesis, non-vascularised tissue (costochondral, sternoclavicular) or vascularised tissue (second metatarsal). Current debate centres around the possibility of alloplastic reconstruction particularly where autogenous tissue has failed. The resultant failure of growth – if this occurs, can be dealt with in late adolescence with either osteotomy, distraction osteogenesis or replacement of the condylar component of the prosthesis.In the adult the choice is currently in favour of alloplastic reconstruction as this gives a more stable long term result and facilitates early mobilisation. Initial cost is clearly an issue, but when weighted against the reduced length of stay and reduced morbidity, often the costs are equivalent in the short term and come to benefit alloplasts in the medium term. Their long term outcomes beyond 15 years are however not clear.